Residue metals and intrinsic moisture in excess sludge improve pore formation during its carbonization process. (January 2020) - Gong, Kedong; Li, Xinyu; Liu, Haoyu; Cheng, Xiang; Sun, Dezhi; Shao, Qian; Dong, Mengyao; Liu, Chuntai; Wu, Shide; Ding, Tao; Qiu, Bin; Guo, Zhanhu
Abstract: Excess sludge, a carbon-rich valuable by-product from wastewater treatment, is utilized as a carbon precursor for synthesizing porous activated carbon. However, improving specific surface area (SBET ) is the main challenge for the sludge derived activated carbon (SAC). In this study, the carbonization process was optimized as following: carbonization temperature of 900 °C, heating rate of 10 °C/min, and dwell time of 30 min. Moreover, the residue heavy metals and bound water remaining in the sludge were demonstrated to be important in the pore formation of the SAC. The metals acted as hard template to form the pores in the SAC after the metals were removed by acid wash. The bound water was found to be soft templates for forming pores due to its evaporation during carbonization. A maximum SBET of 1018.8 m 2 /g was achieved for the SAC when the bound water content was controlled at 2 wt%. Graphical abstract: Image 1